Recent progress in magneto-optics and research on its application - Norimichi Kojima; Kuniro Tsushima (Физика низких температур, 2002)
Various kinds of magneto-optical properties are investigated in rare earth orthochromites. From an analysis of Cr³⁺ exciton absorption in RCrO₃ (R=Tb, Dy, and Ho), it is unferred that these compounds exhibit an anomalous spin-reorientation in a magnetic field along the b axis, where the weak ferromagnetic moment of the Cr³⁺ spins rotates in the ac plane perpendicular to the b axis. In these compounds, when the R³⁺ spin configuration is disordered, an anomalous satellite band appears on the lower-energy side of the Cr³⁺ exciton absorption, which is associated with the breakdown of the k=0 selection rule due to the disorder of the R³⁺ spin configuration. In YbCrO₃, various kinds of cooperative excitations, such as a Cr³⁺ exciton coupled with an Yb³⁺ magnon and a Cr³⁺−Yb³⁺ exciton molecule, which are induced by the antisymmetric exchange interaction between the Cr³⁺ and Yb³⁺ spins, appear in the visible region. The propagation of these cooperative excitations depends strongly on the spin structure and the external magnetic field. In ErCrO₃, a photo-induced spin-reorientation takes place within 50 μs after the photo-irradiation corresponding to the ⁴A2g→²Eg transition of Cr³⁺, and it returns to the initial spin configuration in about 400 ms. This phenomenon is detected in the time-resolved Er³⁺ absorption spectra corresponding to the ⁴I₁₅/₂→⁴I₉/₂ transition. Finally, we briefly review the recent frontier research on applications developed mainly in Japan.